KINERJA PORTOFOLIO SAHAM OPTIMAL DI BURSA EFEK INDONESIA (Berdasarkan Single Index Model dan Stochastic Dominance) - Wulandari, Luh Putu Fiadevi; Sedana, I.B Panji; Purbawangsa, I.B Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
This study directly applying the Single Index Model and Stochastic Dominance to solve the problem of portfolio selection. This study aims to determine the performance difference between the Single Index Model and Stochastic Dominance. The use of secondary data used in this study with a sample selection purposive sampling techniques. When viewed under a single portfolio return index return model is able to produce a portfolio of (1%) and stochastic dominace return of (1.2%). The results showed that the value of the portfolio formation Stochastic Dominance has a higher Treynor index is 6.554% compared to the Single Index Model with Treynor index of 3.423%.
Keywords: Portfolio, Single Index Model, Stochastic Dominance, Treynor Index